Three undescribed nematodes from the coast of Oregon - Murphy, D. G. (Limnology and Oceanography, 1962)
A new subspecies and two new species of free-living marine nematodes, Rhabdodemania minor subsp. oregonensis n. subsp., Synonchiella spiculora n. sp., and Desmodora papillostoma n. sp., are described and illustrated. Type specimens are from a sample taken off the Oregon coast by the Department of Oceanography, Oregon State University.
NeMys doc_id: 5132